2001
DOI: 10.1021/jo010622i
|View full text |Cite
|
Sign up to set email alerts
|

Computational Support for Tunneling in Thermal [1,7]-Hydrogen Shift Reactions

Abstract: Density functional calculations have been performed for the [1,7]-hydrogen shift in two substituted 1,3,5-heptatrienes (1 and 9) for which kinetic data are available from the literature, including the observed kinetic isotope effects. For both cases the computed kinetic isotope effect was significantly smaller than that observed. These results provide further support for the presence of tunneling in thermal, antarafacial [1,7]-hydrogen shift reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Transition state theory 24 (TST) calculations carried out by Hess 22 on Tri at 60 • C led to a KIE of 3.9, which is almost half the experimental value. TST ignores quantum effects, but since the [1,7]-hydrogen shift is a hydrogen transfer reaction, 25 Hess indicated that the discrepancy between both KIEs may be due to quantum mechanical tunneling.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Transition state theory 24 (TST) calculations carried out by Hess 22 on Tri at 60 • C led to a KIE of 3.9, which is almost half the experimental value. TST ignores quantum effects, but since the [1,7]-hydrogen shift is a hydrogen transfer reaction, 25 Hess indicated that the discrepancy between both KIEs may be due to quantum mechanical tunneling.…”
Section: Introductionmentioning
confidence: 91%
“…The similarity between the experimental data indicates that Tri could be a good theoretical model to study the isomerization reaction. 22,23 Scheme 3…”
Section: Introductionmentioning
confidence: 99%
“…81 The B3LYP/6-31G* calculations give activation energies similar to experiment though consistently slightly higher. The calculated primary kinetic isotope effects are substantially smaller than those obtained by experiment, also as expected in systems in which tunnelling occurs.…”
Section: [17] Sigmatropic Rearrangementsmentioning
confidence: 64%
“…On the other hand, for an effective hydride migration a collinear TS with C 2v symmetry cannot be excluded 11. Recently, density functional calculations have been performed by Hess for the thermal [1,7]‐H shift in 1,3,5‐heptatrienes 12. The geometric results of these calculations are in good correspondence with our former 3‐21G/CI‐MP2 calculations of the in‐plane C 2v TS for the [1,5]‐H shift in cis ‐1,3‐pentadiene 4, vide supra.…”
Section: Resultsmentioning
confidence: 99%